Pengaruh BOPO dan NOM Terhadap Return On Equity Pada PT. Bank Syariah Mandiri - muhammad apis daulay (Business Finence Analyst Co.,, 2023)
This research aims to test the variables that affect profitability in PT. Sharia Bank is independent. Site of PT. Bank Mandiri Shariah is a secondary source of data for this investigation. Eviews 10 is used as an estimate tool in quantitative analysis that uses double regression analysis for data time series. Return on Equity (ROE) serves as a data study. Net Operating Margin and Operating Costs for Operating Revenue (BOPO). Use double linear regression for data analysis. T test and hypothesis test. Determination coefficient with test F. Based on the partial test findings (test t), Operational Costs versus Operational Income (BOPO) PT. Sharia Bank has no influence on return on equity (ROE). In the PT. Bank Mandiri Syariah, Net Operating Margin (NOM) Significantly and Affecting Return on Equity (ROE). In addition, the results of simultaneous testing (Test F) showed that BOPO and Net Operating Margin (NOM) influenced Return on Equity (ROE) in PT. Sharia Bank is independent. Keywords: Profitabilitas; Return on Equity; BOPO; Net Operating Margin